The milestones of the life and scientific-pedagogical path of Mikhail Ivanovich Balabolkin (to the 90th anniversary of the birth of Professor M.I. Balabolkin) - Nina A. Petunina; Irina A. Kuzina; Ekaterina V. Goncharova; Narine S. Martirosian; Milena E. Telnova; Mikhail V. Khachaturov (Терапевтический архив)
The article is dedicated to the 90th year of the birth of Professor Mikhail Ivanovich Balabolkin. He was a well-known endocrinologist, Doctor of Medical Science, Director of the Institute of Diabetes of The National Medical Research Center for Endocrinology of the Russian Academy of Medical Sciences, Head of the Departments of Endocrinology at the Moscow Medical and Dental Institute named after N.A. Semashko, and subsequently at the Moscow Medical Academy named after I. M. Sechenov. Mikhail Ivanovich will forever remain in the memory of all his students and colleagues. The article contains not only biographical data on the professor’s professional and scientific activities, the history of the creation of the departments of endocrinology, which he headed, but also memories of people who were well acquainted with Mikhail Ivanovich. Particular attention in the article is paid to the personal qualities of M.I. Balabolkin, his family, attitude towards his professional team and hobbies.